COMPARATIVE ANALYSIS OF MANAGEMENT OF HIGHER EDUCATION SYSTEMS IN SPAIN AND ITALY (Education in the 21st Century, 2023)
The modern world has been largely changed through further civilization and successful development and globalization of all education systems, which was facilitated by the Bologna process. Studying and comparing the experience of managing higher education systems in European countries largely interests the public. Further study of the subject leads to more effective ways of organizing and staging the higher education in other countries. Spain and Italy are example of such states. A comparative analysis of the management of higher education systems in Spain and Italy that emphasizes the unique aspects of the both systems allows to improve higher education in other countries.It is the first time that a comparative analysis of the management of higher education systems in Spain and Italy was conducted in Armenia. It was presented in tables, emphasizing the features, similarities and differences of their governing and financing bodies, ways of entering universities and assessment process, as well as the structure of higher education systems in both countries. As those tables indicate, in these countries both external and internal bodies are responsible for the management of higher education systems. Names of those bodies are different. Both in Spain and in Italian universities, there is “academic freedom” with a highly developed credit system. In both countries there are state and non-state universities licensed by the state. Studying process in the universities of Spain and Italy is conducted both in the native language and in English. The higher education systems of Spain and Italy differ in their methods of assessment, as well as admission to universities. Spanish universities have a 10-point grading system, while Italy has 30-point grading one. For admission to universities in Spain, you must have a diploma of secondary education and entrance exams based on the system called "Selectividad", while foreign applicants must also pass an exam in Spanish. In the case of Italy, the admission to college for Italian citizens is a college certificate without entry exams. As for foreign students, they need to pass exams for admission in the form of an interview. In oppose to Spain where students have to pay tuition for studying in universities, education in Italy is free including for foreign students. A comparative analysis of the management of higher education systems in Spain and Italy highlights some positive elements universities in other countries can use for further development and progress of their higher education system. Studying and comparing the experience of managing higher education systems in European countries such as Spain and Italy is very important. This experience can lead to more effective ways of organization and development of higher education system in other countries.